Multisocietal consensus on the use of cytoreductive surgery and HIPEC for the treatment of epithelial ovarian cancer: a GRADE approach for evidence evaluation and recommendation - Brennan, Donnal; Hawarden, Amy; Cinquini, Michela; Bhatt, Aditi; Somashekhar, Sampige Prasanna; Pompiliu, Piso; Brandl, Andreas; Levine, Edward; Dellinger, Thanh H.; Bakrin, Naoual; Paolo, Sammartino; Rea, Lo Dico; et al. (Journal of surgical oncology, 2025)
Introduction The locoregional treatment of high grade serous ovarian cancer (HGSOC) comprises of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Recent evidence form randomized trials, has led to controversy related to the use of HIPEC in addition to interval CRS (iCRS) and the role of secondary CRS (sCRS) in patients with the first platinum-sensitive recurrence from high-grade serous ovarian cancer (HGSOC). This multi-society consensus, coordinated by the Peritoneal Surface Oncology Group International (PSOGI) with inputs from ISSPP, SSO, ESSO, and IGCS, evaluated the role of these interventions using the GRADE ADOLOPMENT methodology. Patients and Methods An international expert panel reviewed evidence for the use of HIPEC in addition to iCRS in stage 3 high grade serous ovarian cancer (HGSOC) and the role of sCRS for patients with platinum-sensitive recurrent HGSOC. A systematic review assessed randomized controlled trials (RCTs) for recurrence-free survival (RFS), overall survival (OS), safety, and quality of life (QoL). Recommendations were formulated using the GRADE Evidence-to-Decision framework. Results HIPEC in addition to iCRS was strongly recommended based on the results of the OVHIPEC-1 trial, which showed significant benefit in RFS (3.5 months) and OS (12 months) without increasing the grade 3-4 morbidity. For the first platinum-sensitive recurrence, a conditional recommendation was made either for sCRS with systemic therapy or systemic therapy alone, reflecting variability in trial outcomes due to heterogeneity in the patient population in the trials and lack of surgical standardization. Conclusion This consensus highlights the benefits of HIPEC in addition of iCRS and key factors that limit its wide-spread use. It underlines the need for individualized decision-making while selecting patients for sCRS. Future research integrating advanced systemic therapies is essential to refine these recommendations and provide equitable access to these complex locoregional treatments.